Analisis Strategi Pemasaran Guna Memasuki Pasar Online Dalam Menghadapi Persaingan Selama Pandemi Covid-19 pada Bisnis Retail Toko ‘’Bintang’’ - Azril Fikri Hawari; Ety Dwi Susanti (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine the analysis of marketing strategies to enter the online market in the face of competition during the covid-19 pandemic. The type of research conducted is descriptive method. Data collection techniques in this study used observation, in-dept interview methods or in-depth interviews, and documentation. Sources of data from this study are the owner or owner, employee or employee, as well as consumers who have made transactions at the "Star" Store. The results showed that by using the SWOT analysis technique, the "Bintang" store was in quadrant II position. Where in this case the strength factor is more dominant than the weakness while at the same time the threats that come from outside are considered quite large when compared to the existing opportunities. Thus, the strategy that is considered the most effective to be implemented is the diversification strategy. The diversification strategy can be applied by the "Star" Store in order to maintain its business activities by optimizing its strengths to stem and face threats that come from outside the company. Keywords: Marketing Strategy, Online Market, Competition During the Covid-19 Pandemic